The Role and Effectiveness of Insurance and Hedging in Reducing the Risk of Financing Decisions - Makkulau, Andi Runis (Advances in Management & Financial Reporting, 2025)
Purpose: This study examines the role and effectiveness of combining insurance and hedging as complementary strategies for managing financing risk in volatile economic environments. By investigating how these two risk management tools work together, the study aims to provide insights into how companies can optimize their financial stability through integrated risk mitigation. Research Design and Methodology: A systematic literature review (SLR) was conducted to analyze recent research on insurance and hedging within financial risk management frameworks. The study evaluates empirical and theoretical sources to explore the synergy between these strategies and their applicability across different risk scenarios. Findings and Discussion: The findings reveal that insurance protects companies from direct operational risks, such as asset damage and unexpected losses, while hedging mitigates market volatility risks, including interest rate and commodity price fluctuations. The combined use of these tools offers a dual-layered approach, providing comprehensive protection against diverse financial risks. Additionally, the study highlights the importance of regulatory support in facilitating access to these instruments, strengthening corporate resilience and stakeholder confidence. Implications: This research contributes to theory and practice by enhancing understanding of dual-instrument risk management. For managers, the findings serve as a guide for selecting appropriate risk mitigation strategies and balancing cost-efficiency and stability. For policymakers, the study underscores the need for a supportive regulatory environment to implement these strategies effectively. Future research could explore sector-specific applications and long-term effects on corporate performance.